KUALITAS PELAYANAN ONLINE “PENDAFTARAN MANDIRI AKTA TANAH (PERMATA)” DI KANTOR PERTANAHAN KOTA SEMARANG (Studi Kasus Pelayanan Balik Nama Sertifikat Hak Atas Tanah - Ikha Nathalia Puspitasari; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Service quality is the assessment of services from recipients of public services to the organizer, so that in the form of administration, services or goods can satisfy the community. The demands of service recipients and supported by technological sophistication encourage the government to provide services based online. One of the government agencies that implemented it was the Semarang City Land Office, through online services